TEACHING SPEAKING IN PRIMARY SCHOOL - Nizamova Nazokat (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation. This paper focuses on the importance of teaching speaking skills in primary school. Speaking is one of the most essential language skills, as it helps young learners express their thoughts, feelings, and ideas in a foreign language. At the primary level, students learn best through interactive and enjoyable activities. Therefore, the use of games, songs, role-plays, dialogues, and visual aids plays a significant role in developing speaking ability. The paper also highlights the teacher’s role in creating a supportive and motivating classroom environment where pupils are not afraid of making mistakes. Special attention is given to age-appropriate methods that encourage active participation and build learners’ confidence in oral communication. Teaching speaking effectively at an early age lays a strong foundation for further language learning.